2012
DOI: 10.3945/jn.111.147751
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Skeletal Muscle and Fat Mass in Patients with Advanced Cancer Using a Metabolomic Approach

Abstract: Urine and plasma metabolites originate from endogenous metabolic pathways in different organs and exogenous sources (diet). Urine and plasma were obtained from advanced cancer patients and investigated to determine if variations in lean and fat mass, dietary intake, and energy metabolism relate to variation in metabolite profiles. Patients (n = 55) recorded their diets for 3 d and after an overnight fast they were evaluated by DXA and indirect calorimetry. Metabolites were measured by NMR and direct injection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 43 publications
2
27
1
Order By: Relevance
“…The reason why differences in the metabolically active mass, and also in REE, are not reflected in urine and plasma metabolites cannot be explained by our study results. Our results are in line with previous findings of Frisard et al and Stretch et al [24,44] who also did not find any associations between energy metabolism and metabolite profiles. Frisard et al examined only markers of oxidative stress in healthy adults [44].…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…The reason why differences in the metabolically active mass, and also in REE, are not reflected in urine and plasma metabolites cannot be explained by our study results. Our results are in line with previous findings of Frisard et al and Stretch et al [24,44] who also did not find any associations between energy metabolism and metabolite profiles. Frisard et al examined only markers of oxidative stress in healthy adults [44].…”
Section: Discussionsupporting
confidence: 83%
“…Frisard et al examined only markers of oxidative stress in healthy adults [44]. Furthermore, Stretch et al only investigated 63 urine metabolites in advanced cancer patients [24]. Our results based on a multi-platform metabolomics approach in urine as well as in plasma revealed that also in healthy subjects there is no distinct metabolite profile directly associated with REE.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…According to the Human Urine Metabolome Project (32), only few amino acids have been identified as possible oncological markers -alanine (33) and valine (34), associated with lung cancer. The only investigated and commercially used method of using amino acid concentration in urine is represented by Prostarix (Metabolon Inc.).…”
Section: Discussionmentioning
confidence: 99%